The prevalence of chronic endometritis in patients with secondary infertility associated with a caesarean scar niche - Mark A. Kurtser; Natalia M. Egikian; Natalia A. Savelyeva; Olga V. Sinitsyna; Liudmila A. Shestakova (IP Berlin A.V., 2022)
Background. The trend towards an increase in the number of caesarean sections (CS) has led to the fact that many women are more likely to plan a second pregnancy with a caesarean scar niche. According to current data, planning pregnancy with a niche may be associated with a decrease in the likelihood of successful implantation, which is a consequence of the uterine form of secondary infertility. In the context of studying the effect of stagnant contents in the projection of the niche on fertility, it is important to assess the prevalence of chronic endometritis (CE) and use new knowledge to personalize patient management schemes in achieving reproductive goals. Aim. To study the prevalence of CE according to various laboratory diagnostic methods in a group of patients with secondary infertility associated with stagnant contents in the niche projection, compared with a group of fertile patients without stagnant contents in the niche projection; to evaluate the possibilities of the cytological and immunocytochemical (ICC) method for studying the endometrium in the diagnosis of CE in comparison with the histological and immunohistochemical (IHC) method. Materials and methods. The prospective study included 38 patients of reproductive age with a caesarean scar niche, who met the inclusion criteria. After excluding other known factors of secondary infertility, performing ultrasound and/or magnetic resonance imaging of the pelvic organs on the 5th8th day of the menstrual cycle, where the presence/absence of stagnant contents in the projection of the niche was assessed, the patients were divided into 2 groups: group 1 (n=30) patients with secondary infertility in combination with stagnant contents in the niche projection (main group), group 2 (n=8) patients without clinical complaints, without stagnant contents in the projection of a clinically insignificant niche (control group). All patients (n=38) underwent an aspiration pipel biopsy of the endometrium (and, in the presence of stagnant contents in the projection of the niche) under ultrasound control on the 7th10th day of the menstrual cycle. Then a cytological, ICC study (using the CD138 marker), a histological, IHC study of the endometrium (using the CD138 marker) was performed. The statistical study was carried out using the IBM SPSS Statistica v22 program (IBM Corp., USA). Results. In the 1st group (n=30), the prevalence of CE according to cytological and ICC studies was 90% (n=27/30), a normal cytological picture was recorded in 10% (n=3/30); the prevalence of CE according to histological and IHC studies was 80% (n=24/30), of which 37.5% (n=9/24) were diagnosed with an incomplete morphological picture of CE, and 62.5% (n=15/24) a complete morphological picture of CE was revealed, a normal morphological picture was recorded in 20% (n=6/30) of cases. In the 2nd group (n=8), the prevalence of CE according to cytological and ICC studies was 12.5% (n=1/8), a normal cytological picture was recorded in 87.5% (n=7/8); according to histological and IHC studies, CE was not diagnosed, a normal morphological picture was recorded in 100% (n=8/8) of cases. A high degree of consistency of laboratory data was revealed for 2 groups (n=38), p=0.0001. The sensitivity of the cytological method compared with the histological method was 95.83% (95% CI 79.7699.26%), specificity 64.29% (95% CI 38.7683.66%), positive predictive value 82.14% (95% CI 64.4192.12%), negative predictive value 90% (95% CI 59.5898.21%), the accuracy of the cytological method compared to the histological one was 84, 21% (95% CI 68.0693.03%). Conclusion. Secondary infertility in patients with stagnant contents in the projection of caesarean scar niche may be associated with CE. Cytological examination of the endometrium in combination with ICC seems to be a promising method for the laboratory evaluation of CE, given the high correlation with histological and IHC data.